O medicamento e a regulação do gozo do sujeito psicótico: uma questão ética - Susana Cançado Teatini (2014)
In the present dissertation one investigates the hypothesis according to which the pharmacological treatment, by itself, is not sufficient to deal with the real of the jouissance of the psychotic subject. In order to do so, one brings forth clinical fragments of a case in which a paranoid patient questioned, through his passages to the act, the treatment which wasoffered by the CERSAM (Mental Health Service), reduced to a psychopharmacological protocol. The research is built upon the intersection of the work bonds that were established between Psychoanalysis, Mental Health, and Law, aiming to formalize the use of psychopharmaceuticals, their successful effects and their limits in the approach of the psychopathological manifestations. One proposes a debate on the therapeutic resource to psychopharmaceuticals in the mental health clinic, conceived from the point of view of the Brazilian Psychiatric Reform. One also reviews the psychoanalytical theory departing from the Freudian discovery of the unconscious and from the Lacanian considerations on body and jouissance. Thus, one revisits the psychoanalytic notions that unfolded the research regarding the jouissance of the psychotic subject, its regulation, a possible stabilization, and the function of medication in treatment direction. Some clinical fragments review of a case shows us that the psychoanalytical oriented interventions enabled not only a different relation betweensubject and medicament, but also a location of the jouissance, its regulation, as well as the opening of a new way out a small invention in face of the real of the Others jouissance.